Niraparib Maintenance Therapy in Platinum-Sensitive, Recurrent Ovarian Cancer - Mansoor R. Mirza; Bradley J. Monk; Jørn Herrstedt; Amit M. Oza; Sven Mahner; Andrés Redondo; Michel Fabbro; Jonathan A. Ledermann; Domenica Lorusso; Ignace Vergote; Noa Ben-Baruch; Christian Marth; et al. (2016)
Background Niraparib is an oral poly(adenosine diphosphate [ADP]-ribose) polymerase (PARP) 1/2 inhibitor that has shown clinical activity in patients with ovarian cancer. We sought to evaluate the efficacy of niraparib versus placebo as maintenance treatment for patients with platinum-sensitive, recurrent ovarian cancer. Methods In this randomized, double-blind, phase 3 trial, patients were categorized according to the presence or absence of a germline BRCA mutation (gBRCA cohort and non-gBRCA cohort) and the type of non-gBRCA mutation and were randomly assigned in a 2:1 ratio to receive niraparib (300 mg) or placebo once daily. The primary end point was progression-free survival. Results Of 553 enrolled patients, 203 were in the gBRCA cohort (with 138 assigned to niraparib and 65 to placebo), and 350 patients were in the non-gBRCA cohort (with 234 assigned to niraparib and 116 to placebo). Patients in the niraparib group had a significantly longer median duration of progression-free survival than did those in the placebo group, including 21.0 vs. 5.5 months in the gBRCA cohort (hazard ratio, 0.27; 95% confidence interval [CI], 0.17 to 0.41), as compared with 12.9 months vs. 3.8 months in the non-gBRCA cohort for patients who had tumors with homologous recombination deficiency (HRD) (hazard ratio, 0.38; 95% CI, 0.24 to 0.59) and 9.3 months vs. 3.9 months in the overall non-gBRCA cohort (hazard ratio, 0.45; 95% CI, 0.34 to 0.61; P<0.001 for all three comparisons). The most common grade 3 or 4 adverse events that were reported in the niraparib group were thrombocytopenia (in 33.8%), anemia (in 25.3%), and neutropenia (in 19.6%), which were managed with dose modifications. Conclusions Among patients with platinum-sensitive, recurrent ovarian cancer, the median duration of progression-free survival was significantly longer among those receiving niraparib than among those receiving placebo, regardless of the presence or absence of gBRCA mutations or HRD status, with moderate bone marrow toxicity. (Funded by Tesaro; ClinicalTrials.gov number, NCT01847274 .).